2004
DOI: 10.1183/09031936.04.00118404
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin reduces the severity of bronchial hyperresponsiveness in patients with asthma

Abstract: A randomised double-blind placebo-controlled study was designed to evaluate the effects of a semisynthetic macrolide antibiotic, clarithromycin, on bronchial hyperresponsiveness to methacholine in patients with a diagnosis of asthma.Adult asthma patients undergoing treatment with budesonide 400 mg b.i.d. and salbutamol 200 mg p.r.n. less than twice weekly were studied. Arm A (16 males/six females, aged 48 ¡ 16 yrs) received clarithromycin 250 mg b.i.d. for 8 weeks, arm B (eight males/12 females, aged 42¡12 yrs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 25 publications
(35 reference statements)
1
71
0
6
Order By: Relevance
“…The possibility of chronic infection with organisms that are sensitive to macrolides provides a strong rationale for their use in asthma, although macrolides may also function as steroid-sparing or antiinflammatory agents [51,52]. Early studies have reported conflicting results [53][54][55][56][57].…”
Section: Asthmamentioning
confidence: 99%
“…The possibility of chronic infection with organisms that are sensitive to macrolides provides a strong rationale for their use in asthma, although macrolides may also function as steroid-sparing or antiinflammatory agents [51,52]. Early studies have reported conflicting results [53][54][55][56][57].…”
Section: Asthmamentioning
confidence: 99%
“…Patients taking oral or inhaled corticosteroid were excluded. The second study examined asthmatics taking 800 mg budesonide daily; serum-free cortisol levels showed no change from baseline levels after treatment with clarithromycin, suggesting that altered steroid metabolism was not the effect mechanism [47]. Evidence for reduced bronchial hyperresponsiveness has also been demonstrated after treatment with erythromycin, roxithromycin and azithromycin [55][56][57].…”
Section: Asthmamentioning
confidence: 99%
“…Two studies have shown significant reductions in bronchial hyperresponsiveness in patients with asthma after 8 weeks' treatment with clarithromycin; neither showed any significant change in FEV1 [47,50]. The first study examined 17 patients with allergy-induced asthma and demonstrated a significant reduction in blood and sputum eosinophil counts, suggesting a possible anti-inflammatory role for clarithromycin [50].…”
Section: Asthmamentioning
confidence: 99%
“…Although it is known that macrolides possess such properties, it is difficult to independently assess the immunomodulatory and antimicrobial effects. Administration of macrolides has been shown to be beneficial in patients with chronic pulmonary inflammatory diseases, including diffuse panbronchiolitis [48], cystic fibrosis [49] and asthma [50]. Whether macrolides also exert favourable immunomodulatory effects during acute pulmonary infection is less clear.…”
Section: Macrolide Antibioticsmentioning
confidence: 99%